2002
DOI: 10.1034/j.1600-0420.80.s236.23.x
|View full text |Cite
|
Sign up to set email alerts
|

CT and a echography of optic nerve in glaucoma

Abstract: In 2001, for the first time in its life, the AISG is holding its Annual Meeting far away from its traditional venue, i.e. Rapallo.The explanation for this decision on the part of its Directive Council, approved, moreover, enthusiastically, by the great majority of its members, lies, in my opinion, in two good reasons: 1 the concomitant IGS with the weight of its programme and the number of participants, as well as the outstanding names present; 2 the attractive beauty of this famous city of Prague, so full of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
13
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 6 publications
1
13
0
Order By: Relevance
“…Quantified Diameters of ON and CSF Sheath During Straight Gaze (0°) and 30°A bduction mean values 1,2,4,[13][14][15]17,18,24,25. Diameters between 1.9 mm and 3.5 mm (ON) and between 2.9 mm and 4.4 mm (CSF sheath) can be found in literature, which are similar to the results given in…”
supporting
confidence: 85%
See 2 more Smart Citations
“…Quantified Diameters of ON and CSF Sheath During Straight Gaze (0°) and 30°A bduction mean values 1,2,4,[13][14][15]17,18,24,25. Diameters between 1.9 mm and 3.5 mm (ON) and between 2.9 mm and 4.4 mm (CSF sheath) can be found in literature, which are similar to the results given in…”
supporting
confidence: 85%
“…Noninvasive diagnosis of the ON sheath by means of ultrasonography has been described in several studies. [1][2][3][4][5][6][7]13,14 However, ultrasonography is known to depend on personal experience and be subjected to interobserver and test-retest variability. Previous studies using MRI techniques for investigation of the ON typically suffered from long acquisition times of between 4 minutes and 15 minutes, 8 -12,15-19 which may lead to artifacts and degradation of spatial resolution caused by the motion of the eyes during the long measurement times.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Beatty et al 18 found a mean OND of 2.86 mm in normal and 2.58 mm in glaucomatous eyes using B-scan sonography. Boles Carenini et al 19 applied A-scan sonography and computed tomography in two similar cohorts. Using sonography, they observed an OND of 2.50 mm in normal and 2.28 mm in glaucomatous eyes.…”
mentioning
confidence: 98%
“…(82) Thinning of the retrobulbar optic nerve has been reported both in histological and diagnostic imaging studies suggesting that the diameter of the nerve may correlate with the extent of the optic atrophy. (83)(84)(85)(86)(87) High-resolution magnetic resonance imaging (MRI) using an ultra fast HASTE-sequence at 3 T sequences of the optic nerve can portray axonal loss in the optic nerve comparing closely with the retinal nerve fiber layer-related parameters and could be used as a biomarker for axonal loss in glaucoma. (82) 3-T diffusion tensor imaging of the optic nerve in patients with glaucoma displays good correlation with the retinal nerve fiber layer thickness measured by OCT and may serve as a biomarker of disease severity.…”
Section: Neurodegenerative Markersmentioning
confidence: 99%